2013
DOI: 10.1111/1365-2745.12048
|View full text |Cite
|
Sign up to set email alerts
|

Complex plant–soil interactions enhance plant species diversity by delaying community convergence

Abstract: Summary 1.A plant that causes specific changes to soil biota may either positively or negatively affect the performance of the plant that subsequently grows in that location. These effects, known as plant-soil feedback, can affect plant species diversity at multiple spatial scales. 2. It has been hypothesized that positive plant-soil feedback reduces alpha (local) diversity by allowing dominance by early-arriving species, but increases gamma (regional) diversity by promoting community divergence (increased bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 43 publications
6
79
0
2
Order By: Relevance
“…It remains unclear how well niche components explain historical contingency at the community level involving many species. Another study provides a hint as to what may happen in more species-rich communities (Fukami & Nakajima 2013). This computer simulation study indicated that high variation in impact niche and requirement niche among species [e.g., as observed among plant Schematic representation of (a) niche components, including overlap, impact, and requirement, and (b) how they are hypothesized to influence the strength of priority effects.…”
Section: Species Traitsmentioning
confidence: 91%
See 1 more Smart Citation
“…It remains unclear how well niche components explain historical contingency at the community level involving many species. Another study provides a hint as to what may happen in more species-rich communities (Fukami & Nakajima 2013). This computer simulation study indicated that high variation in impact niche and requirement niche among species [e.g., as observed among plant Schematic representation of (a) niche components, including overlap, impact, and requirement, and (b) how they are hypothesized to influence the strength of priority effects.…”
Section: Species Traitsmentioning
confidence: 91%
“…Conversely, fire-sensitive species may prevent creation of the niche for fire-resistant species by, for example, keeping local patches moist. More generally, by modifying soil conditions in various ways (Kardol et al 2007, van de Voorde et al 2011, plant species can create niches for a different set of plant species, driving communities onto alternative transient trajectories (Fukami & Nakajima 2013). Similarly, in the marine environment, coraland alga-dominated states, or mussel-and alga-dominated states, have been indicated to represent alternative stable states (Knowlton 2004, Petraitis et al 2009).…”
Section: Niche Modificationmentioning
confidence: 99%
“…However, there is accumulating evidence that inhibitory soil biota may have particularly strong negative density-or frequency-dependent effects on productivity at low diversity by infecting conspecifics that are in close proximity to each other, and thus reducing per capita and ecosystem-level plant growth (Bever et al 1997;Knops et al 1999;Klironomos 2002;Mitchell et al 2002;Kulmatiski et al 2008). In more diverse communities, however, soil-borne disease may be less prevalent because there is a lower likelihood of growing near a conspecific, and there are lower concentrations of host-specific soil enemies (Mitchell et al 2002;Brandt et al 2013;Fukami and Nakajima 2013). These effects could act in concert with more traditional resource-based mechanisms: pathogen attack in low-diversity assemblages could reduce productivity at the low end of diversity, while niche complementarity could simultaneously increase productivity at high ends of diversity.…”
Section: Discussionmentioning
confidence: 99%
“…We constructed a model following the methods developed by Mouquet et al () and modified by Fukami and Nakajima (, ) for simulating establishment, reproduction, and death of sessile organisms competing for local resources. In our model, individuals represented terrestrial plants, but the model should be applicable to other taxa characterized by dispersing propagules (seeds or larvae) and sessile adults that modify local environmental conditions in ways that alter species competitiveness.…”
Section: Methodsmentioning
confidence: 99%
“…Well‐documented examples of organism–environment feedbacks include those between plants and soil conditions (Bever et al ) and metabolic cross‐feeding among microbial populations (Rozen et al , Harcombe ). Such feedbacks have long been a subject of ecological research, and an increasing number of studies indicate that they can influence a range of ecological phenomena, including the maintenance of species diversity (Odling‐Smee et al , Bever et al ), the trajectory of community succession (Kardol et al , Jiang and DeAngelis ), the generation of priority effects (Kardol et al ), the spread of invasive species (Levine et al , Eppstein and Molofsky ), and the emergence of long‐term transient community states (Fukami and Nakajima , ). However, the role of organism–environment feedbacks is poorly understood in the context of habitat loss and fragmentation.…”
mentioning
confidence: 99%